THE ROLE OF TECHNOLOGY IN MODERN TEACHING (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
Technology has revolutionized education by offering cutting-edge resources to improve student performance. This study investigates the effects of technology integration on academic achievement, teacher effectiveness, and student involvement. Data from 150 high school students and 20 teachers were gathered through surveys and interviews using a mixed-method approach. The findings show that when technology is in line with educational objectives, it greatly increases performance and engagement. Distractions and the digital divide, however, continue to be problems. This essay highlights the significance of infrastructure development and teacher preparation while offering insights on successfully utilizing technology in the classroom.
Keywords: Technology, cutting-edge resources, academic achievement, mixed-method approach, digital divide, infrastructure development.